TRAINING METHODS IN PUBLIC SECTOR CASE OF ASIA - Seyed Kamal (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Training is an effort to increase the knowledge, skills, and abilities of employees and managers so they can better do their jobs. The principles of learning must be considered in all training activities for officials. In a good training program the main objective is the change in the behaviour of staff in order to achieve performance improvement. But the main question is what kind of changes are needed? A possible answer would be changes that support a capacity of building a framework for innovation and entrepreneurship abilities of officials in the administration system and public administration. This research is an attempt to discuss the question and provide an answer. By using a research literature review and an expert analysis approach, needs definitions, and utilization of national needs of the public sector, the findings were categorized into functions and recommendations. Also the paper deals with the success of the South Korean pioneer training system (NHI) which is an important and top priority center for Korean government, so the paper deals with the strategies and objectives of NHI.